Implementation of Anti-Fraud and Mediation Strategies as Alternative Dispute Resolution in Islamic Banks: Approaches and Impacts - Andi Fariana; Trinandari Nugrahanti (Research Synergy Foundation, 2022)
Abstract Along with the growth of Islamic banks, the level of problems faced by Islamic banks has also increased. One thing that should be observed is the occurrence of fraud in various forms. If this happens, fast and appropriate steps are needed so that fraud can be detected and the problem resolved early on because fraud that occurs if it is not immediately addressed and drags on, the potential for loss and harm to the community (customers) is very large and ultimately leads to on the loss of public trust in Islamic banks. Financial Services Authority Regulation No. 39/POJK.03/2019 concerning the Implementation of the Anti-Fraud Strategy, it is sufficient to regulate the strengthening of the internal control system and to balance it, a dispute resolution pattern is needed without eliminating the bank's obligation to report and supervise. mediation, which is actually hinted at in the Qur'an with the term Al Shulhu, is an alternative so that disputes can be simultaneously resolved. The mediation model offered is to mediate internally within banking institutions by independent mediators who are appointed and become members of the BPS (Sharia Supervisory Board). is through litigation institutions, namely the Religious Courts.